Food and nutrition consumption pattern vis-Ã -vis healthcare aptitude among farming households of north Indian plains - MURALIKRISHNAN, LAKSHMANAN; SANGEETHA, V; BARUA, SUKANYA; CHOUDHARY, ANIL K; DASS, ANCHAL; SINGH, PREMLATA (The Indian Journal of Agricultural Sciences, 2020)
Hygienic food consumption, household sanitation and healthcare aptitude are some of the important concerns in rural India specifically among the farming households. Hence, it should be ensured that rural masses who exert more physically must take healthy food complying with required safety and sanitation measures for higher physical efficiency in farming and household chores. Thus, in order to assess the food and nutrition consumption pattern as well as healthcare aptitude among farming households of north Indian plains, the current study was undertaken in two representative districts of north Indian plains, viz. Bhagpat (UP) and Jhajjar districts (Haryana). Under this study, a total of 50 respondents of each district were selected by multistage random sampling technique (MRST) in two states of Uttar Pradesh (UP) and Haryana. The MRST study revealed that majority of farming households emphasized upon safety food consumption practices (72–92%) and household sanitation (32–94%). However, healthy food and nutrition consumption habits (12–92%), physical access to food and nutrition facilities (24–100%) as well as access to healthcare facilities (12–96%) in their household vicinity revealed a moderate response among the farming households in the study area. A fair number of respondents found to posses ill-habits (alcoholism and smoking) which should be avoided by changing their mindset by mass awareness promotional programmes. Overall, current MRST study concluded that farming households of Haryana and Western UP follow sound safe food and nutrition consumption practices; however, the food and nutrition consumption habits, sanitation and healthcare facilities/services need greater attention of community and development agencies to ensure better food, nutrition, sanitation and healthcare among farming households of north Indian plains.